Book Review: Metal health in English Language Education - Rosyid Akhul Muslim (IRecall Journal, 2025)
Mental Health in English Language Education responds to the growing concern over mental health issues among adolescents and their significant impact on education. Through an interdisciplinary approach combining education, psychology, and cultural studies, the book provides practical strategies and teaching materials for integrating mental health topics into English language classrooms. It highlights the role of English education in fostering mental health literacy through cultural, linguistic, and literary lenses. The book addresses current challenges such as digital media influence, climate anxiety, gender issues, and academic pressure, aiming to empower educators and create inclusive, supportive learning environments. This review outlines the book’s strengths in offering relevant pedagogical frameworks and discusses its limitations regarding generalizability across diverse educational and cultural contexts.